2016
DOI: 10.1063/1.4971997
|View full text |Cite
|
Sign up to set email alerts
|

Speckle contrast reduction of laser light using a chiral nematic liquid crystal diffuser

Abstract: High coherence in laser light causes spatially distributed interference called speckle. In applications such as holographic projection, this undesirable side effect degrades image clarity. The current methods of speckle reduction, such as a rotating ground-glass diffuser, require additional bulky moving parts. Here, we present an alternative technology based upon a compact, electrohydrodynamic chiral nematic liquid crystal device. A spatially random phase modulation of the incident light is achieved through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…1 ; however, they still preserves a high-level spatial coherence so coherent speckles cannot be sufficiently reduced 21 . In order to suppress the effective spatial coherence of the conventional lasers, rotating optical diffusers 16 , colloidal solutions 17 , micro electro-mechanical mirrors 18 , or chiral nematic liquid crystal diffusers 19 have been introduced to the illumination path; these techniques, however, requires mechanical moving parts generating vibration noise or a longer acquisition time, which mitigates the advantages (See CNLC in Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ; however, they still preserves a high-level spatial coherence so coherent speckles cannot be sufficiently reduced 21 . In order to suppress the effective spatial coherence of the conventional lasers, rotating optical diffusers 16 , colloidal solutions 17 , micro electro-mechanical mirrors 18 , or chiral nematic liquid crystal diffusers 19 have been introduced to the illumination path; these techniques, however, requires mechanical moving parts generating vibration noise or a longer acquisition time, which mitigates the advantages (See CNLC in Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…‘Investigation zone’ indicates the tunable temporal and spatial coherence area demonstrated in this investigation. NBL: narrowband laser 21 , 30 , BBL: broadband laser 21 , 29 , 31 , ASE: amplified spontaneous emission 21 , 22 , RL: random laser 21 , 22 , LEDs: light emitting diodes 21 , 30 , 32 , T: thermal sources 21 , 30 , 32 , SFWL: spatially filtered white light 21 , 28 , 30 , 32 , DGL: degenerate laser with pinhole inside the cavity 23 , CNLC: chiral nematic liquid crystal 19 , LD w/wo SD/MD: a laser diode with and without a static diffuser (SD) and a moving diffuser (MD) with a specific diffusion angle (DA). …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed that a positive dielectric anisotropy chiral nematic LC with a pitch of 250 nm and doped with an ionic dopant (cetyltrimethylammonium bromide—CTAB ) can cause a spatially and temporally random phase perturbation to incident laser light when operated in a dynamic scattering mode by subjecting the LC to a low frequency (< 100 Hz) square wave electric field of sufficiently large amplitude 22 . The random perturbation to the phase of light can, in turn, result in a reduction in the observed speckle contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Several solutions are proposed based on the temporal decoherence approach, for example, mechanically vibrating or rotating an optical component such as diffuser, microlens array, phase matrix and/or optical fibers [8][9][10][11][12]. Motionless approaches have also been demonstrated by using a polymer dynamic diffraction grating, colloidal suspension, spatial light modulator, ferroelectric liquid crystal (LC), LC with chiral dopant, and nanoparticle (NP)-doped LC devices [13][14][15][16][17][18]. While the solution of using a moving diffuser is mostly selected due to its low cost and effectiveness, motionless approaches are of high interest, since they eliminate the risk of mechanical failure in products.…”
Section: Introductionmentioning
confidence: 99%